HATL5: a cell surface serine protease differentially expressed in epithelial cancers. - Gregory S Miller; Gina L Zoratti; Andrew S Murray; Christopher Bergum; Lauren M Tanabe; Karin List (PLoS ONE, 2014)
Over the last two decades, cell surface proteases belonging to the type II transmembrane serine protease (TTSP) family have emerged as important enzymes in the mammalian degradome, playing critical roles in epithelial biology, regulation of metabolic homeostasis, and cancer. Human airway trypsin-like protease 5 (HATL5) is one of the few family members that remains uncharacterized. Here we demonstrate that HATL5 is a catalytically active serine protease that is inhibited by the two Kunitz type serine protease inhibitors, hepatocyte growth factor activator inhibitor (HAI)-1 and 2, as well as by serpinA1. Full-length HATL5 is localized on the cell surface of cultured mammalian cells as demonstrated by confocal microscopy. HATL5 displays a relatively restricted tissue expression profile, with both transcript and protein present in the cervix, esophagus, and oral cavity. Immunohistochemical analysis revealed an expression pattern where HATL5 is localized on the cell surface of differentiated epithelial cells in the stratified squamous epithelia of all three of these tissues. Interestingly, HATL5 is significantly decreased in cervical, esophageal, and head and neck carcinomas as compared to normal tissue. Analysis of cervical and esophageal cancer tissue arrays demonstrated that the squamous epithelial cells lose their expression of HATL5 protein upon malignant transformation.